2018
DOI: 10.1001/jamapediatrics.2018.0315
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Acid-Suppressive Medications and Antibiotics During Infancy and Allergic Diseases in Early Childhood

Abstract: IMPORTANCE Allergic diseases are prevalent in childhood. Early exposure to medications that can alter the microbiome, including acid-suppressive medications and antibiotics, may influence the likelihood of allergy. OBJECTIVE To determine whether there is an association between the use of acid-suppressive medications or antibiotics in the first 6 months of infancy and development of allergic diseases in early childhood. DESIGN, SETTING, AND PARTICIPANTS A retrospective cohort study was conducted in 792 130 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
214
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(230 citation statements)
references
References 46 publications
7
214
3
6
Order By: Relevance
“…Most studies, which have been carried out on antibiotic use during pregnancy and infancy, found an increased risk for asthma, whereas our results only provide evidence for a weak positive association after antibiotic use in the first year of life but not with prenatal exposure. Discrepancies in these findings might be explained by different outcome definitions.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Most studies, which have been carried out on antibiotic use during pregnancy and infancy, found an increased risk for asthma, whereas our results only provide evidence for a weak positive association after antibiotic use in the first year of life but not with prenatal exposure. Discrepancies in these findings might be explained by different outcome definitions.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar to our results, several studies found significant positive associations between atopic dermatitis and antibiotic exposure in utero 12,13 or in the first year of life. [14][15][16] In contrast, the study by Bisgaard et al,17 where in contrast to our study only children of mothers with history of asthma were included, did not see an increased risk for atopic dermatitis after maternal use of antibiotics in pregnancy. Dom et al, 13 who defined atopic dermatitis as parent-reported symptoms, did not find a relationship with antibiotics in the first year of life.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…During in utero development and later in life, there are several direct and indirect factors that affect healthy microbiota colonization and subsequent host-microbiota interactions. These factors include mother's health status (Stokholm et al, 2018), diet (Frei et al, 2012;Barcik et al, 2015), transfer of maternal antibodies and microbial molecules (Gomez de Ag€ uero et al, 2016;Koch et al, 2016), mode of delivery (Bosch et al, 2016), and breastfeeding and early-life environment (day care, siblings [Wolsk et al, 2016], pets at home [Sitarik et al, 2018;Tun et al, 2017], traditional farm-like dust at home [Stein et al, 2016;Kirjavainen et al, 2019], and smoking and antibiotic and other drug usage in pregnancy and early childhood [Mitre et al, 2018;Loewen et al, 2018]).…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…Increasing use of antibiotics has been linked with dysbiosis and enhanced prevalence of allergies and asthma . Also, the pharmacologic impairment of gastric digestion is associated with gut dysbiosis and has been correlated with allergy in mice and humans . However, study results of probiotic supplementation in childhood asthma or wheeze are inconclusive …”
Section: Introductionmentioning
confidence: 99%